2020
DOI: 10.1073/pnas.2003724117
|View full text |Cite
|
Sign up to set email alerts
|

Genome mapping of a LYST mutation in corn snakes indicates that vertebrate chromatophore vesicles are lysosome-related organelles

Abstract: Reptiles exhibit a spectacular diversity of skin colors and patterns brought about by the interactions among three chromatophore types: black melanophores with melanin-packed melanosomes, red and yellow xanthophores with pteridine- and/or carotenoid-containing vesicles, and iridophores filled with light-reflecting platelets generating structural colors. Whereas the melanosome, the only color-producing endosome in mammals and birds, has been documented as a lysosome-related organelle, the maturation paths of xa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 79 publications
1
45
0
Order By: Relevance
“…Overall, pigment organelles of crab spiders join the growing list of pigment LROs in distantly-related animals, including mammalian melanosomes (3), insect ommochromasomes and pterinosomes (43), fish pterinosomes (44), lepidopteran riboflavin and uric acid granules (45, 46), as well as snake melanosomes, pterinosomes and iridosomes (4). Our study therefore provides another piece of evidence that all pigment organelles, from invertebrates to vertebrates, share a common intracellular identity, as postulated 40 years ago by Bagnara and colleagues (2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, pigment organelles of crab spiders join the growing list of pigment LROs in distantly-related animals, including mammalian melanosomes (3), insect ommochromasomes and pterinosomes (43), fish pterinosomes (44), lepidopteran riboflavin and uric acid granules (45, 46), as well as snake melanosomes, pterinosomes and iridosomes (4). Our study therefore provides another piece of evidence that all pigment organelles, from invertebrates to vertebrates, share a common intracellular identity, as postulated 40 years ago by Bagnara and colleagues (2).…”
Section: Discussionmentioning
confidence: 99%
“…Bagnara and colleagues postulated in 1979 that all pigment organelles of vertebrates derive from a common primordial organelle (2). Since then, an increasing body of evidence has shown that pigment organelles, from mammal melanosomes to snake pterinosomes, belong to the lysosome-related organelle (LRO) family (3, 4). LROs intersect the endolysosomal system (5), which forms a complex and active network of membrane-bound compartments produced by endocytic and secretory pathways (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our current knowledge of the genetics of vertebrate colouration comes primarily from studies on model species, particularly the mouse (e.g. Baxter et al 2004; Hoekstra 2006; San-Jose and Roulin 2017; but see Ullate-Agote et al 2020). This bias in the literature provides a limited view of the ways in which genetic variation can affect vertebrate colouration.…”
Section: Introductionmentioning
confidence: 99%
“…The extensive phenotypic variation in pigment and pattern found in captive-bred ball pythons can therefore help correct the bias (e.g. Ullate-Agote et al 2020) associated with mammalian models and melanin-based pigmentation in the scientific literature on vertebrate colouration.…”
Section: Introductionmentioning
confidence: 99%